2016
DOI: 10.1007/978-3-319-41252-8_4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School Climate and Teacher Quality on Mathematics Achievement: A Difference-in-Differences Approach

Abstract: The aim of the study was to investigate causal effects of aspects of teacher quality and school climate on mathematics achievement through use of country-level longitudinal data. By investigating within-country change over time, biasing influence from omitted variables in the form of fixed country characteristics is avoided, thereby increasing the likelihood of making correct causal inferences. Data from 38 countries participating in both TIMSS 2007 and TIMSS 2011 were analyzed with structural equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 10 publications
5
22
0
4
Order By: Relevance
“…Both TIMSS andIEA's Teacher Education andDevelopment Study in Mathematics (TEDS-M, conducted in 2007-2008) have included many questions, asking teachers to report on their preparedness to teach particular topics. Although Luschei and Chudgar (2011) and Gustafsson and Nilson (2016) found that these items had a weak direct relationship to student achievement across countries, other studies have suggested that readiness is related to instructional quality (Blomeke et al 2016), as well as content knowledge and content preparation (Schmidt et al 2017), suggesting that instructional quality may have an indirect effect on student learning.…”
Section: Teacher Content Knowledgementioning
confidence: 93%
“…Both TIMSS andIEA's Teacher Education andDevelopment Study in Mathematics (TEDS-M, conducted in 2007-2008) have included many questions, asking teachers to report on their preparedness to teach particular topics. Although Luschei and Chudgar (2011) and Gustafsson and Nilson (2016) found that these items had a weak direct relationship to student achievement across countries, other studies have suggested that readiness is related to instructional quality (Blomeke et al 2016), as well as content knowledge and content preparation (Schmidt et al 2017), suggesting that instructional quality may have an indirect effect on student learning.…”
Section: Teacher Content Knowledgementioning
confidence: 93%
“…Begrepet undervisningskvalitet defineres på ulike måter innenfor pedagogikk og fagdidaktikk, men i TIMSS studien måles undervisningskvalitet ut fra en laerers evne til å vaere god klasseleder, til å vaere støttende og til å gi tydelige instruksjoner og kognitivt utfordrende oppgaver i undervisningen (Bergem, Nilsen & Scherer, 2016). Flere andre studier har også vist at gode kunnskaper i faget laereren underviser i er viktig for å gi god undervisning og et godt laeringsutbytte for elevene (Abell, 2007;Driel, Berry, & Meirink, 2014;Gustafsson & Nilsen, 2016;Herold & Waring, 2017;Monk, 1994;Wayne & Youngs, 2003). I forskningsgjennomgangen av Abell (2007) ser en flere eksempler på at et lavt naturfagnivå hos laereren gir mer laererstyrt undervisning med mindre grad av elevdeltakelse og fokus på begrepsutvikling.…”
Section: Tidligere Forskning På Laererutdanningers Betydning For Kompunclassified
“…Noen studier har konkludert med at økt fagkompetanse over et visst nivå (bachelor eller master), ikke gir høyere laeringsutbytte hos elevene (McKenzie et al, 2005;Monk, 1994;Wilson et al, 2001). De fleste av disse studiene er imidlertid gjort på høyere klassetrinn (Gustafsson & Nilsen, 2016). Det finnes imidlertid studier av laerere på lavere trinn i grunnskolen som viser at mangel på fagkunnskaper gir laerere som blant annet følger laererboka i større grad, stiller få utforskende spørsmål og i liten grad gjennomfører kognitivt utviklende aktiviteter (Abell, 2007;Driel et al, 2014;Harlen, 1997).…”
Section: Tidligere Forskning På Laererutdanningers Betydning For Kompunclassified
See 1 more Smart Citation
“…Two significant lines of research in educational psychology are the study of (a) characteristics of school climate and educational system, and (b) motivational processes, such as intrinsic motivation, persistence, and academic self-efficacy. Studies have found that both school climate and student motivation are consistently associated with academic achievement (Gustafsson & Nilsen, 2016;Hardre & Reeve, 2003;Roeser & Eccles, 1998;Scherer & Nilsen, 2016). However, while current research provides valuable insight into how school climate and innovative educational systems impact academic achievement, less is known about the mechanisms that link innovative educational systems based on psychological theories with academic achievement, and in particular the mediating role of motivation in this process.…”
Section: Introductionmentioning
confidence: 96%